Integration Facilities for Pedestrians in Train Station Area - Dicky Virgiawan Rukmana; Siti Maemunah; Anisa Mahadita Candrarahayu; Reza Digambiro; Ram Agustina Manurung; Rezha Rahandhi (Institut Transportasi dan Logistik Trisakti, 2022)
This study aims to determine the characteristics of pedestrians, the level of pedestrian service, the performance of pedestrian facilities, and the level of walkability in Bekasi train station area. This study uses several analytical techniques, described as follows: Pedestrian Analysis; Walkability Index; and Importance Performance Analysis (IPA). 100 respondents based on probability sampling technique. The results of the analysis show that pedestrian infrastructure is lacking and inadequate for pedestrians in segments 1 and 2. Segments 3, 4, and 5 already have adequate infrastructure for pedestrians. Importance performance analysis shows that there are indicators that require priority treatment. The indicators are considered very important by pedestrians, however based on pedestrian analysis and the walkability index obtained low ratings.